Sense and Accessibility: Understanding People with Physical Disabilities’ Experiences with Sensing Systems - Kane, Shaun; Guo, Anhong; Morris, Meredith Ringel (ASSETS 2020, 2020)
Sensing technologies that implicitly and explicitly mediate digital experiences are an increasingly pervasive part of daily living; it is vital to ensure that these technologies work appropriately for people with physical disabilities. We conducted on online survey with 40 adults with physical disabilities, gathering open-ended descriptions about respondents’ experiences with a variety of sensing systems, including motion sensors, biometric sensors, speech input, as well as touch and gesture systems. We present findings regarding the many challenges status quo sensing systems present for people with physical disabilities, as well as the ways in which our participants responded to these challenges. We conclude by reflecting on the significance of these findings for defining a future research agenda for creating more inclusive sensing systems.
Best Paper Nominee